Biosynthesis of Silver Nanoparticles using Ajuca ive Leaf Extract and Assessment of their Activity on E. coli and Streptococcus bacteria - Sasi, Mariam Mohammed; Hribesh, Samira Omar; Eshkourfu, Rabia Omar; Amara, Rokaya Omar (European Scientific Journal, ESJ, 2025)
Silver nanoparticle synthesis from plant extracts has been widely used in medicine, particularly as an antibacterial agent. In the present study, Ajuca ive leaf extract was performed using an aqueous solution tested for its phytochemical components. The results of the phytochemical analysis of Ajuca ive leaf extract had alkaloids, carbohydrates, proteins, flavonoids, phenols, saponins, and coumarins. Synthesis of silver nanoparticles was performed using Ajuca ive leaf extract with a 1 mM solution of silver nitrate. The synthesized silver nanoparticles were characterized with UV-visible spectroscopy, X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), Energy-dispersive X-ray spectroscopy (EDX), and Fourier Transform Infra-Red (FTIR) spectrum. SEM analysis revealed the size of the AgNPs of 36 nm, 55 nm, 70 nm, 100, and 300 nm. The EDX study showed that the optical absorption peak was detected at 3 keV, the characteristic peak for the absorbed metallic silver nanoparticles. FTIR analysis identified the possible functional group involved in reducing silver metal ions into silver nanoparticles. In addition, the antibacterial activity of synthesized silver nanoparticles was also examined and the results showed good antibacterial activities against E. coli and Streptococcus bacteria.